The effect of non-contributory pensions on saving in Mexico - Jorge Alonso Ortiz; Catalina Amuedo Dorantes; Laura Juarez (Inter-American Development Bank (IDB), 2016)
This paper examines the effects of non-contributory pension programs at the federal and state levels on Mexican households' saving patterns using micro data from the Mexican Income and Expenditure Survey. The federal program by itself appears to reduce the saving rate of households whose oldest member is either 18 to 54 or 65 to 69. State programs by themselves have no significant effects on household saving rates in the smallest localities, but in larger localities they may reduce the saving of households with members in their sixties. The combination of both types of programs generally does not have statistically significant effects on households' aggregate saving, probably because each program seems to affect different population strata. No significant effects are found for households whose oldest member is age-eligible (70 and older). Within specific investment categories, evidence is found of increases in human capital and in durable and financial goods for some age groups. Finally, the paper provides evidence on household-level labor supply responses.
Keywords: D14; J26; O12; H55; 330; Non-contributory pensions; Saving; Mexico